THE EFFECT OF COMPLEMENTARY THERAPY COMBINATION OF ERGONOMIC EXERCISE AND MUSIC (SERASI) TO LOWER BLOOD PRESSURE IN THE ELDERLY: CASE STUDY - Putri Regina Aulia; Lita Heni Kusumawardani; Saryono Saryono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Introduction: Elderly are people who have reached the age of more than 60 years and have experienced natural changes, both physical changes and changes related to the disease process. Elderly people tend to have a higher risk of experiencing degenerative diseases due to decreased body function. One of the diseases that is often suffered by the elderly is hypertension. Management to overcome hypertension can be done non-pharmacologically with complementary therapy, namely a combination of ergonomic gymnastics and music therapy (Serasi). Purpose: This study aims to determine the effect of combination therapy of ergonomic gymnastics and music therapy (Serasi) on reducing blood pressure in the elderly. Methods: The research method used is case study method. This intervention was given to 3 elderly with hypertension. The intervention was carried out for 3 days with a duration of ± 30 minutes per day. Data analysis used in this study used the Wilcoxon test. Discussion: Client's blood pressure after being given the intervention decreased with an average blood pressure of 158 mmHg (systolic) and 89.89 mmHg (diastolic). The Wilcoxon test results obtained a Sig. (2-tailed) value for systolic of 0.007 and diastolic of 0.017 where this value is <0.05. There is a significant effect of providing a combination of ergonomic gymnastics and music therapy (Serasi) on blood pressure in elderly hypertensive patients.